Limited Role for the DsrA and RprA Regulatory RNAs in rpoS Regulation in Salmonella enterica - Jones, Amy M. (American Society for Microbiology, 2006)
RpoS, the sigma factor of enteric bacteria that responds to stress and stationary phase, is subject to complex regulation acting at multiple levels, including transcription, translation, and proteolysis. Increased translation of rpoS mRNA during growth at low temperature, after osmotic challenge, or with a constitutively activated Rcs phosphorelay depends on two trans-acting small regulatory RNAs (sRNAs) in Escherichia coli. The DsrA and RprA sRNAs are both highly conserved in Salmonella enterica, as is their target, an inhibitory antisense element within the rpoS untranslated leader. Analysis of dsrA and rprA deletion mutants indicates that while the increased translation of RpoS in response to osmotic challenge is conserved in S. enterica, dependence on these two sRNA regulators is much reduced. Furthermore, low-temperature growth or constitutive RcsC activation had only modest effects on RpoS expression, and these increases were, respectively, independent of dsrA or rprA function. This lack of conservation of sRNA function suggests surprising flexibility in RpoS regulation.